ChemInform Abstract: Heavier Group 2 Grignard Reagents of the Type Aryl‐ae(L)n‐X (Post‐Grignard Reagents). Issue 23 (10th June 2014) - Westerhausen, Matthias; Langer, Jens; Krieck, Sven; Fischer, Reinald; Goerls, Helmar; Koehler, Mathias
Abstract Review: 181 refs.